Applications of topology in automobile engineering - P. Palanichamy2, P. Srinivasan1* (Journal of Experimental Sciences, 2010)
Topology is a branch of Geometry concerned with the properties remain unchanged when the figure is deformed. Topology is used in automobile engineering, computer science engineering and other fields. The significance of topology is given in the following pages which will help to develop light weight components which are used in manufacturing two wheeler carts etc, the result is we get better automobile fuel efficiency. This in turn results to energy conservation and global environmental preservation. In industries several attempts are made to produce light weight designs. In order to manufacture light weight component our first step is to decrease the weights of hub bearing. Many companies have succeeded to reduce the weights of various products. By applying shape optimization techniques, many have dramatically succeeded in reducing weights. Our main objective is to reduce the weight of a hub-bearing of a car. To achieve this target we make use of topological optimization technique as well as shape optimization technique. <div style="BORDER-RIGHT: medium none; PADDING-RIGHT: 0in; BORDER-TOP: medium none; PADDING-LEFT: 0in; PADDING-BOTTOM: 1pt; BORDER-LEFT: medium none; PADDING-TOP: 0in; BORDER-BOTTOM: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt"><p class="MsoNormal" style="BORDER-RIGHT: medium none; PADDING-RIGHT: 0in; BORDER-TOP: medium none; PADDING-LEFT: 0in; PADDING-BOTTOM: 0in; MARGIN: 0in 0in 0pt; BORDER-LEFT: medium none; PADDING-TOP: 0in; BORDER-BOTTOM: medium none; TEXT-ALIGN: justify; mso-layout-grid-align: none; mso-padding-alt: 0in 0in 1.0pt 0in; mso-border-bottom-alt: solid windowtext .5pt">Keywords: Shape optimization, contractible, decomposition, quotient topology P. P. Srinivasan1*, P. Palanichamy2 <div style="BORDER-RIGHT: medium none; PADDING-RIGHT: 0in; BORDER-TOP: medium none; PADDING-LEFT: 0in; PADDING-BOTTOM: 1pt; BORDER-LEFT: medium none; PADDING-TOP: 0in; BORDER-BOTTOM: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt"><p class="MsoNormal" style="BORDER-RIGHT: medium none; PADDING-RIGHT: 0in; BORDER-TOP: medium none; PADDING-LEFT: 0in; PADDING-BOTTOM: 0in; MARGIN: 0in 0in 0pt; BORDER-LEFT: medium none; PADDING-TOP: 0in; BORDER-BOTTOM: medium none; TEXT-ALIGN: justify; mso-layout-grid-align: none; mso-padding-alt: 0in 0in 1.0pt 0in; mso-border-bottom-alt: solid windowtext .5pt">1Kamban Engineering College, Thiruvannamalai, Anna University, 606 603 India; 2Professor of Mathematics, Kamban Engineering College, Thiruvannamalai, Anna University, 606 603 India* Corresponding Author, Email: seenu_kec@yahoo.co.in Cite This Article As: P. Srinivasan, P. Palanichamy. 2010. Applications of topology in automobile engineering. J. Exp. Sci. 1(1): 21-24.